Effects of acepromazine or dexmedetomidine on fentanyl disposition in dogs during recovery from isoflurane anesthesia. (5th May 2015) - Keating, Stephanie; Kerr, Carolyn; McDonell, Wayne; Valverde, Alexander; Johnson, Ron; Knych, Heather; Edginton, Andrea
Abstract: Objective: To describe fentanyl pharmacokinetics during isoflurane anesthesia and on recovery from anesthesia with concurrent administration of acepromazine, dexmedetomidine or saline in dogs. Study design: Experimental blinded, randomized, crossover study. Animals: Seven adult hound dogs. Methods: Dogs were administered intravenous (IV) fentanyl as a bolus (5 μg kg −1 ) followed by an infusion (5 μg kg −1  hour −1 ) for 120 minutes during isoflurane anesthesia and emergence from anesthesia, and for 60 minutes after extubation during recovery from anesthesia. At the time of extubation, dexmedetomidine (2.5 μg kg −1 ), acepromazine (0.05 mg kg −1 ) or saline were administered IV. Venous blood was sampled during the maintenance and recovery periods. Fentanyl plasma concentrations were measured using high‐performance liquid chromatography–mass spectrometry and population pharmacokinetic analyses were performed. Results: Mean fentanyl plasma concentrations were 1.6–4.5 ng mL −1 during isoflurane anesthesia and 1.6–2.0 ng mL −1 during recovery from anesthesia. Recovery from isoflurane anesthesia without sedation was associated with an increase in the volume of the central compartment from 0.80 to 1.02 L kg −1 . After administration of acepromazine, systemic clearance of fentanyl increased from 31.5 to 40.3 mL minute −1  kg −1 and the volume of the central compartment increased from 0.70 to 0.94 L kg −1 . Administration of dexmedetomidine did not significantly change fentanyl pharmacokinetics. Inter‐individual variability for fentanyl parameter estimates in all treatments ranged from 2.2% to 54.5%, and residual error ranged from 6.3% to 13.4%. Conclusions and clinical relevance: The dose rates of fentanyl used in this study achieved previously established analgesic plasma concentrations for the duration of the infusion. Despite alterations in fentanyl pharmacokinetics, differences in fentanyl plasma concentrations among treatments during recovery from anesthesia were small and were unlikely to be of clinical significance.